Long-term Outcome of Children with Ureteropelvic Junction Obstruction: Thirty-one years’ Experience at a Tertiary Teaching Hospital in South Africa. - Nyandat, Joram; Kala, Udai (Journal of Pediatric Nephrology, 2019)
Background and Aim: Being the most common pathologic cause of hydronephrosis in children, we characterized and evaluated the long-term outcome of Ureteropelvic junction obstruction (UPJO) at a tertiary hospital in South Africa Methods: Children confirmed to have UPJO between 1985 and 2016 were characterized based on demographic and baseline clinical data. Long term outcomes were need for surgical intervention, loss to follow up rates, anthropometric measures, renal outcomes (Glomerular Filtration Rate and Blood pressure). Results: Of 107 children, 74.8% were male, 47% had hydronephrosis identified antenatally, 47.7% had the left kidney unilaterally affected, 31.8% had an additional urogenital anomaly, 19.6% presented with an abdominal mass, and 37.4% had a urinary tract infection. On enrolment, 54.2% and 30.8% had normal systolic and diastolic BP, 59.8% had normal BMI for age and 72% had normal length/height for age. The median follow-up time was 35(9.0 - 191.0) months, 65% had surgery with a median time to surgery of 2 (0 - 6.8) months. Children lost to follow-up had a higher proportion of extrinsic causes of UPJO (12.0% vs. 0%, P=0.041) and other urogenital anomalies (38.7% vs. 15.6%, P=0.019). There was no significant effect of time or surgical intervention on mean BMI and height for age, blood pressure percentile and eGFR for age. Conclusion: In our setting, UPJO has an early presentation, with an early time to surgery. Long-term outcome is favorable, but loss to follow-up presents a significant drawback that needs to be addressed. Keywords: Ureter; Hypertension; Congenital anomalies of kidney and urinary tract; CAKUT; Urological Diseases; Hydronephrosis.